Multiple Functions and Mechanisms Underlying the Role of METTL3 in Human Cancers - Zheng, Wenhui; Dong, Xiaoshen; Zhao, Yan; Wang, Shuo; Jiang, Haiyang; Zhang, Mingdi; Zheng, Xinyu; Gu, Ming (Frontiers in Oncology, 2019)
Methyltransferase-like 3 (METTL3), a predominantly catalytic enzyme in the N6-methyladenosine (m6A) methyltransferase system, is dysregulated and plays a dual role ( oncogene or tumor suppressor) in different human cancers. The expression and pro- or anticancer role of METTL3 in different cancers remain controversial. METTL3 is implicated in many aspects of tumor progression, including tumorigenesis, proliferation, invasion, migration, cell cycle, differentiation, and viability. Most underlying mechanisms involve multiple signaling pathways that rely on m6A-dependent modification. However, METTL3 can also modulate the cancer process by directly promoting the translation of oncogenes via interaction with the translation initiation machinery through recruitment of eukaryotic translation initiation factor 3 subunit h (eIF3h). In this review, we summarized the current evidence on METTL3 in diverse human malignancies and its potential as a prognostic/ therapeutic target.